2016
DOI: 10.1097/pas.0000000000000548
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Cytokeratin 7 Immunohistochemistry in Cervical Low-grade Squamous Intraepithelial Lesion as a Marker for Risk of Progression to a High-grade Lesion

Abstract: The squamocolumnar junction (SCJ) cell population of the uterine cervix is a discrete epithelial area and the putative source of the majority of high-grade squamous intraepithelial lesions (HSIL). The SCJ cells can be identified by immunohistochemical (IHC) stains including cytokeratin 7 (CK7). Others have theorized that an SCJ marker-positive low-grade squamous intraepithelial lesion (LSIL) has a higher risk for future HSIL compared with an SCJ marker-negative LSIL. This study has 2 aims: first, to refine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…SCJ cells have been recognised as ‘embryonic’ cells which are thought to be uniquely susceptible to oncogenic HPV infection, and therefore to be the origin for cervical carcinoma and its precursors. SCC and HSIL invariably involve the SCJ and frequently display positive staining for CK7 while CK7 positive LSIL has a high risk for future HSIL . The ‘top‐down’ differentiation model suggests that the SCJ cells in the uterine cervix can give rise to a second population of metaplastic progeny, the subjacent basal/reserve cells, with a shift from the SCJ‐positive to ‐negative immunophenotype (negative CK7) .…”
Section: Discussionmentioning
confidence: 99%
“…SCJ cells have been recognised as ‘embryonic’ cells which are thought to be uniquely susceptible to oncogenic HPV infection, and therefore to be the origin for cervical carcinoma and its precursors. SCC and HSIL invariably involve the SCJ and frequently display positive staining for CK7 while CK7 positive LSIL has a high risk for future HSIL . The ‘top‐down’ differentiation model suggests that the SCJ cells in the uterine cervix can give rise to a second population of metaplastic progeny, the subjacent basal/reserve cells, with a shift from the SCJ‐positive to ‐negative immunophenotype (negative CK7) .…”
Section: Discussionmentioning
confidence: 99%
“…However, this remains an elusive association, not a cause [8,10]. Cytokeratin 7 has been used as a marker for low-grade squamous cervical lesions with high risk of progression [11]. Case 1 had benign squamous colonic tissue that resembled esophageal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being actively involved in adult adaptive processes (metaplasia, hyperplasia) [10], SC junction cells exhibit intriguing phenotypic similarities with approximately 90% of cervical SCC and high-grade precursors [9,12]. These findings underlying the instrumental role of junctional cells in cervical carcinogenesis were recently confirmed by several immunohistochemical and/or transcriptional studies analyzing the expression of SC junction-overexpressed biomarkers (i.e., cytokeratin 7 (Krt7), anterior gradient protein 2 (AGR2) or cystic fibrosis transmembrane conductance regulator (CFTR)) in large cohorts of cervical (pre)neoplastic lesions [13,14,15,16,17]. Moreover, the evidence that normal-appearing SC junction cells harbor both HPV transcripts (E6*I/II) and early viral proteins (HPV E2) was reported and sustains the possibility that these cuboidal cells could serve as a reservoir for latent infections and subsequent CIN development in asymptomatic HPV-positive patients [18].…”
Section: Introductionmentioning
confidence: 93%
“…Recently, four studies analyzed the predictive value of junctional biomarkers (especially Krt7) and, interestingly, all showed that low-grade CIN arising from the SC junction have a significantly higher risk to progress to CIN2/3 compared to their counterparts observed in the transformation zone/ectocervix [12,13,14,15]. Furthermore, when compared to other risk factors, such as HPV16 infection and diffuse p16 ink4 expression, full-thickness Krt7 immunoreactivity demonstrated the highest correlation with lesion progression [14].…”
Section: Dualistic Model Of Hpv-related Carcinogenesismentioning
confidence: 99%